Candidate Genes Involved in the Biosynthesis of Triterpenoid Saponins in Platycodon grandiflorum Identified by Transcriptome Analysis - Ma, Chun-Hua; Gao, Zheng-Jie; Zhang, Jia-Jin; Zhang, Wei; Shao, Jian-Hui; Hai, Mei-Rong; Chen, Jun-Wen; Yang, Sheng-Chao; Zhang, Guang-Hui (Frontiers in Plant Science, 2016)
Background: Platycodon grandiflorum is the only species in the genus Platycodon of the family Campanulaceae, which has been traditionally used as a medicinal plant for its lung-heat-clearing, antitussive, and expectorant properties in China, Japanese and Korean. Oleanane-type triterpenoid saponins were the main chemical components of P. grandiflorum and platycodin D was the abundant and main bioactive component, but little is known about their biosynthesis in plants. Hence, P. grandiflorum is an ideal medicinal plant for studying the biosynthesis of Oleanane-type saponins. In addition, the genomic information of this important herbal plant is unavailable. Principal Findings: A total of 58,580,566 clean reads were obtained, which were assembled into 34,053 unigenes, with an average length of 936 bp and N50 of 1,661 bp by analyzing the transcriptome data of P. grandiflorum. Among these 34,053 unigenes, 22,409 unigenes (65.80%) were annotated based on the information available from public databases, including Nr, NCBI, Swiss-Prot, KOG and KEGG. Furthermore, 21 candidate cytochrome P450 genes and 17 candidate UDP-glycosyltransferase genes most likely involved in triterpenoid saponins biosynthesis pathway were discovered from the transcriptome sequencing of P. grandiflorum. In addition, 10,626 SSRs were identified based on the transcriptome data, which would provide abundant candidates of molecular markers for genetic diversity and genetic map for this medicinal plant. Conclusion: The genomic data obtained from P. grandiflorum, especially the identification of putative genes involved in triterpenoid saponins biosynthesis pathway, will facilitate our understanding of the biosynthesis of triterpenoid saponins at molecular level.